Budesonide Induces Favourable Histologic and Symptomatic Recovery in Patients with Non-responsive and Refractory Coeliac Disease When Given in an Open Capsule Format - Daniel Saitta; Lee M Henneken; Pragalathan Apputhurai; Swee Lin Chen Yi Mei; Jason A. Tye-Din (2024)
Non-responsive coeliac disease (NRCD), where symptoms and enteropathy persist despite a prolonged gluten-free diet (GFD), is common. Refractory coeliac disease (RCD), characterised by malabsorption and extensive enteropathy, is rare but serious. In both, treatment options are limited. Topical budesonide may help and an open capsule format promoting proximal small intestinal delivery may be advantageous.